Risk Analysis of Occupational Safety and Health Analysis Using the HIRARC Method at Building Construction - Pramesthi, Shifa Ardhelia; Anwar, Ruslin; Susanti, Lilya (ASTONJADRO, 2025)
Occupational health and safety in Indonesia are crucial for improving worker safety and reducing the high incidence of construction-related accidents. In the research conducted on the construction of the Joint Lecture Building at a University in Malang City, a comprehensive analysis will be carried out to manage OHS risks, minimize workplace accidents, and improve work safety. By identifying hazards from each task and determining risks, risk controls for this construction project will be obtained. The work to be studied includes lower structure and upper structure tasks of the project. The research results show that risk control using the HIRARC method identified 52 hazards and risks. The risk analysis for lower structure tasks revealed five extreme risks, ten moderate risks, and four low risks, while the risk analysis for upper structure tasks revealed eight extreme risks and twenty-five moderate risks. The dominant hazard identification factors were machine-related, with seventeen hazard identifications dominated by heavy equipment hitting workers. The second factor was material-related risks, with workers being struck by falling materials and stepping on sharp objects. The third factor was worker-related risks, with seven identified risks dominated by workers falling from heights, followed by work method-related risks with seven identified risks dominated by improper worker positioning causing health issues. The final factor was environmental, with seven identified hazards dominated by landslides. Risk control is divided based on the causes of hazards, namely man, machine, material, method, and environment. Risk control is carried out by identifying based on the five HIRARC control hierarchy levels: elimination, substitution, engineering control, administrative control, and PPE.